Knowledge, Attitudes and Beliefs towards Electronic Cigarettes among University Students in Austria. (13th November 2019) - Paudyal, P; Movia, M
Abstract: Background: The popularity of e-cigarette is increasing recently, both as an alternative nicotine delivery tool or smoking cessation aid. Austria is a country with a high smoking prevalence; 28% of the population are current smoker and 21% have tried e-cigarettes at least once. In this current context, it is important to understand the opinion regarding e-cigarettes. Methods: This cross-sectional survey examined the use, knowledge, attitudes and beliefs towards e-cigarettes among undergraduate students from Carinthia University of Applied Sciences in Austria. The anonymous questionnaire was handed out in 29 classrooms during compulsory lecturers, and completed questionnaire was returned to a provided box in the front of the classroom. Descriptive summary statistics was used to summarize the results using SPSS 24. Statistical significance was considered at p < 0.05. Results: A total of 528 students were approached and all returned the questionnaire giving a 100% completion rate. 83.7% were female and half (50.2%) were in the age group 20 and 24. 96.6% of students reported being aware of e-cigarettes and 32.4% mentioned trying e-cigarettes at least once. 71.2% reported of ever smoking tobacco. 53.8% disagreed that e-cigarettes are an effective way for smoking cessation and only 10.3% agreed recommending it to a friend or family for smoking cessation. 78.1% believed that e-cigarettes are harmful to the health of those who use them and 58.2% disagreed that the use of e-cigarettes should be prohibited on University Campus premises. Conclusions: To our knowledge, this study is the first of its kind performed in Austria. Our study shows that self-reported ever use of e-cigarettes is 1.5 times higher among this population than among the general population in Austria. Majority of participants disagreed that e-cigarettes are an effective way for smoking cessation. There seems a gap in knowledge regarding the e-cigarette which needs to be addressed among the university students. Key messages: In Austria, e-cigarettes use is 1.5 times higher among university students compared to the general population. Knowledge gap regarding e-cigarettes needs to be addressed among the university students.